SOCI 2100: Principles of Sociology - Wortham, Robert (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
COURSE DESCRIPTIONThis course is designed to help stimulate your sociological imagination and allow you to practice the sociologist=s craft. You will be introduced to several of the different theoretical perspectives that sociologists utilize to gain a better understanding of society as well as important methodological tools that can be employed to test knowledge claims. Instead of providing a general review of the literature, this course will invite you to conduct an in depth investigation of key sociological concepts like inequality, culture, social change, deviance, socialization and demographic processes. Welcome to the sociological journey.